Ideal Anatomic Location for Saphenous Nerve Block for Foot and Ankle Surgeries: A Prospective Randomized Clinical Evaluation. Issue 4 (16th October 2019) - Henrikson, Karl; Adhikary, Sanjib; Pace, Gregory; Liu, Wai; Juliano, Paul; Aydogan, Umur
Category: Regional anesthesia for foot and ankle surgery Introduction/Purpose: Regional anesthesia has resulted in significant improvements in patient outcomes including reduced postoperative pain, opioid consumption, opioid-related adverse effects, and decreased postoperative length of stay. Saphenous nerve blocks provide distal analgesia while minimizing the reduction in quadriceps strength seen with more proximal femoral nerve blocks. Saphenous nerve blocks may be performed at the mid-thigh with the subsartorial technique or just proximal to the knee with the transsartorial technique. The present study compares these two techniques in terms of analgesia effectiveness and quadriceps motor preservation. Methods: This study was approved by our institutional IRB committee. A power analysis was conducted prior to the study. Patients, aged 18 to 65, were prospectively identified from a list of elective foot and ankle surgeries performed by one of the study investigators. Preoperatively, bilateral isometric knee extension strength was measured, and subjects completed a PROMIS global health survey. The surgeon was blinded to the randomization of patients to proximal or distal blocks. Bilateral isometric knee extension strength was reassessed following the block as well as sensation, post-operative visual analogue pain score (VAS), and subjective satisfaction. Due to non-normality of the sample, the Wilcoxon rank-sum test was employed to analyze continuous variables such as strength measures. For categorical variables such as gender, pain score, and patient satisfaction, the Pearson chi- square test was used. Results: Twenty-four patients (24 lower extremities) were enrolled in the study and 12 randomized to each group. The two groups were not significantly different in age, gender, or pre-operative PROMIS Mental and Physical Summary Scores. The nerve block procedure was successfully performed in a single attempt in all cases. The VAS was not significantly different at 2 in the distal group and 3 in the proximal group. In each group 11 patients were totally satisfied with the block and 1 was moderately satisfied. The knee extension strength decreased in both the operative and non-operative lower extremity following administration of the nerve block. When normalized to the effect in the non-operative extremity, there was no significant difference in strength decrease between the two groups (p=0.89). Conclusion: This randomized, single-blinded trial compared proximal subsartorial saphenous nerve block with distal transsartorial saphenous nerve block outside of the adductor canal. There was no significant difference in the efficacy of the two techniques was observed in terms of VAS pain score or patient satisfaction and no difference in post-operative weakness. This is the first randomized trial on saphenous nerve blocks to normalize strength to the non-operative lower extremity, reducing the confounding effect of peri-operative narcotic and sedative medications. This study offers evidence for equivalence of the subsartorial and transsartorial saphenous nerve block techniques.